Reining in the “Junior Varsity Congress”: A Call for Meaningful Judicial Review of the Federal Sentencing Guidelines - Joseph W. Luby (Washington University Law Quarterly, 1999)
Part II presents a brief history of federal sentencing reform, including the rise of judicial and academic dissatisfaction with the Guidelines. To provide a context for the administrative law prescriptions that I propose, Part II reviews some of the Commission’s more questionable judgments. Part III details and criticizes the limited judicial review surrounding the Commission’s implementation of its statutory mandates. Part III focuses upon “statutory review”— the side-by-side comparison of Guidelines provisions with the statutory commands that govern them. It begins with an administrative law framework against which the Guidelines might be evaluated, tracing the rise and fall of the Chevron principle, under which a court will accept an agency’s interpretation of a statute as long as the agency has “reasonably” interpreted the statute. Part III then describes and analyzes the various means by which the Guidelines have been challenged as inconsistent with their enacting legislation. I have examined 312 such challenges from 1988 through 1997, the first full ten years during which the Guidelines operated. Part III ultimately confirms the SRA’s status as a forgotten source of law, a status that prevents the courts from ensuring the agency’s fealty to the statute it administers.
Keywords: Sentencing guidelines (Criminal procedure); Judicial review of administrative acts; United States Sentencing Commission; Sentencing Reform Act of 1984